Coastal buoy data acquisition and telemetry system for monitoring oceanographic and meteorological variables in the Gulf of Mexico. (October 2021) - Martínez-Osuna, Juan F.; Ocampo-Torres, Francisco J.; Gutiérrez-Loza, Lucía; Valenzuela, Ernesto; Castro, Angel; Alcaraz, Rodrigo; Rodríguez, Carlos; Ulloa, Luis R.
Abstract: This paper presents a data acquisition and telemetry system designed and built to monitor oceanographic and meteorological parameters. A voltage regulator and readout module was designed for the reading of data from a set of dedicated commercial sensors and to continuously monitor the voltage level of the power supply. In order to monitor the measured parameters and the status of the buoy remotely, a data string was transmitted every hour using an Iridium satellite transceiver. The described system was implemented and tested in four coastal oceanographic buoys that were deployed and operated in remote sites in the Gulf of Mexico (GoM) for several months in 2016. The data recorded by the buoys is used to describe the oceanographic and meteorological conditions at each site. The system proved to be reliable for long-term monitoring at offshore sites, requiring only minor corrective maintenance during their operation in the field. Highlights: A data acquisition and telemetry system was designed for environmental applications. A voltage regulator module was designed for the electrical protection of the system. The data storage and control software is run by an i.MX6 core on-board computer. The telemetry system takes advantage of the low-orbit Iridium constellation. The system was successfully implemented on 4 coastal oceanographic buoys in 2016.